Analysis of Groundwater Biological Parameters in Ponjong District, Gunung Kidul Regency, Special Region of Yogyakarta - Sari, Avellyn Shinthya; Kusumayudha, Sari Bahagiarti; Suharsono, Suharsono; Prasetyadi, Corolus (Journal of Applied Sciences, Management and Engineering Technology, 2023)
This study shows that the condition of the well water tested based on physical, chemical and biological parameters to determine the feasibility of the water used by the surrounding community still meets the required quality standard thresholds. Although somewhat polluted because of the mining. Underground water in the karst area of Gunungkidul Regency is safe as raw water for drinking by residents and meets the standards set by the Indonesian Ministry of Health and Government Regulation Number 82 of 2001 concerning Water Quality Management and Water Pollution Control. If used as drinking water, it still has to go through water treatment or be heated to a certain boiling point, because it contains bacteria that may be harmful to humans.